Cost of primary care approaches for hypertension management and risk-based cardiovascular disease prevention in Bangladesh: a HEARTS costing tool application - Andrew E Moran; Sohel Reza Choudhury; Deliana Kostova; Muhammad Jami Husain; Mohammad Sabbir Haider; Mahfuzur Rahman Bhuiyan; Renesa Tarannum; Shamim Jubayer (BMJ Open)
Objective To estimate the costs of scaling up the HEARTS pilot project for hypertension management and risk-based cardiovascular disease (CVD) prevention at the full population level in the four subdistricts (upazilas) in Bangladesh.Settings Two intervention scenarios in subdistrict health complexes: hypertension management only, and risk-based integrated hypertension, diabetes, and cholesterol management.Design Data obtained during July–August 2020 from subdistrict health complexes on the cost of medications, diagnostic materials, staff salaries and other programme components.Methods Programme costs were assessed using the HEARTS costing tool, an Excel-based instrument to collect, track and evaluate the incremental annual costs of implementing the HEARTS programme from the health system perspective.Primary and secondary outcome measures Programme cost, provider time.Results The total annual cost for the hypertension control programme was estimated at US$3.2 million, equivalent to US$2.8 per capita or US$8.9 per eligible patient. The largest cost share (US$1.35 million; 43%) was attributed to the cost of medications, followed by the cost of provider time to administer treatment (38%). The total annual cost of the risk-based integrated management programme was projected at US$14.4 million, entailing US$12.9 per capita or US$40.2 per eligible patient. The estimated annual costs per patient treated with medications for hypertension, diabetes and cholesterol were US$18, US$29 and US$37, respectively.Conclusion Expanding the HEARTS hypertension management and CVD prevention programme to provide services to the entire eligible population in the catchment area may face constraints in physician capacity. A task-sharing model involving shifting of select tasks from doctors to nurses and local community health workers would be essential for the eventual scale-up of primary care services to prevent CVD in Bangladesh.